2015
DOI: 10.18632/oncotarget.4175
|View full text |Cite
|
Sign up to set email alerts
|

Marine alkaloid Monanchocidin a overcomes drug resistance by induction of autophagy and lysosomal membrane permeabilization

Abstract: Monanchocidin A (MonA) is a novel alkaloid recently isolated from the marine sponge Monanchora pulchra. The compound reveals cytotoxic activity in genitourinary cancers including cisplatin-sensitive and -resistant germ cell tumor (GCT) cell lines, hormone-sensitive and castration-resistant prostate carcinoma cell lines and different bladder carcinoma cell lines. In contrast, non-malignant cells were significantly less sensitive. MonA is highly synergistic with cisplatin in GCT cells. Induction of autophagy at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 50 publications
4
86
0
Order By: Relevance
“…Western blotting was performed as described before . Total protein extracts (20–30 µg/sample) were subjected to electrophoresis in SDS‐polyacrylamide gels at 120 V, and transferred from gel to a 0.2 µm pore PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed as described before . Total protein extracts (20–30 µg/sample) were subjected to electrophoresis in SDS‐polyacrylamide gels at 120 V, and transferred from gel to a 0.2 µm pore PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The medium was changed with medium containing FrA (1 µM). After 48 h of incubation cells were fixed and permeabilized as described before . After washing with PBS, samples were treated with 1: 400 rabbit anti‐LC3B‐I/II antibody solution (in 0.1% (w/v) NaN 3 ; 0.2% (w/v) BSA in PBS, pH 7.4) overnight at 4°C, washed with PBS and incubated with secondary anti‐rabbit Alexa Fluor 488‐conjugated antibody solution in PSB for 1 h at RT.…”
Section: Methodsmentioning
confidence: 99%
“…40 However, Dyshlovoy et al reported that monanchocidin A ( 24 ) displayed up to 4-fold higher potency against several cancer cell lines than non-malignant cell lines. 47 Monanchocidin A ( 24 ) was also equally active in cisplatin-sensitive and -resistant germ cell tumor (GCT) cell lines. Strong synergistic effects of combined treatment of monanchocidin A ( 24 ) and cisplatin were observed as well 47 …”
Section: Toxicity and General Sar Picturementioning
confidence: 99%
“…47 Monanchocidin A ( 24 ) was also equally active in cisplatin-sensitive and -resistant germ cell tumor (GCT) cell lines. Strong synergistic effects of combined treatment of monanchocidin A ( 24 ) and cisplatin were observed as well 47 …”
Section: Toxicity and General Sar Picturementioning
confidence: 99%
See 1 more Smart Citation